Louisa Stuart Costello - Saunders, Clare Broome. author. aut Link
XI, 254 p.
Keywords: Louisa Stuart Costello (1799-1870) was a critically acclaimed poet, novelist, travel writer, historian, and artist. Here, Broom Saunders provides a wealth of extracts from her diverse writings, a rich source of information about the pioneering career of a professional woman writer, and insight into a nineteenth-century writing life.